Descriptive analysis using R for age trend in dengue cases / Nor Farisha Muhamad Krishnan ... [et al.] - Muhamad Krishnan, Nor Farisha; Ahmad Zukarnain, Zuriani; Jamaludin, Marhainis; Abdul Rahman, Noorihan (Universiti Teknologi MARA, Perlis, 2020)
Dengue is a viral infection disease transmitted by Aedes mosquitoes which can lead to fatality. The case study is conducted for Kota Bharu city which is the capital city of Kelantan State in Malaysia. Different areas in Kota Bharu recorded different number of cases. The aim of this study is to see whether there is a trend in age range for those who are infected by dengue. Data on dengue cases from 2015 until 2019 were obtained from Department of Health in Kelantan. We have done descriptive analysis on range of age among the infected victims using R programming. The data visualization presented that victims from the age range between 10 years old and 35 years old were the most common in area Kubang Kerian and Panji with 20.3% and 19.7% respectively. Nevertheless, gender was not a factor for dengue cases. The mean age is 30.17 years and 28.38 years old for both ranges correspondingly. Dengue outbreak was also affected by the age of victims and has a significant health problem primarily in adolescents and young adults. Public awareness and proper vector control are needed to keep the dengue cases low and to prevent outbreaks.